Amyloid-β/Tau burden and neuroinflammation dual-targeted nanomedicines synergistically restore memory and recognition of Alzheimer's disease mice. (April 2023) - Zhang, Lingxiao; Hou, Shengjie; Movahedi, Fatemeh; Li, Zijin; Li, Li; Hu, Jing; Jia, Yingbo; Huang, Yaru; Zhu, Jie; Sun, Xiaoying; Zeng, Linghui; Liu, Ruitian; et al.
Abstract: Efficient multi-targeted intervention of complex pathogenic factors may hold promises for Alzheimer's disease (AD) treatment due to the continuous failure of single-targeted therapy in clinics. To this end, we developed two dual-targeted layered double hydroxide (LDH) nanoparticle (NP)-based nanomedicines in this research for simultaneously reducing amyloid β (Aβ)/hyperphosphorylated Tau burden and neuroinflammation. LDH NPs were first loaded with two therapeutics, i.e. Rutin and β-site amyloid precursor protein cleaving enzyme-1 (BACE1) or glycogen synthase kinase 3β (GSK3β) siRNA. The nanomedicines were further functionalized with Ang2 and RVG29 via adsorption of their bovine serum albumin (BSA) conjugates. In APP/PS1 and Tau.P301S AD mouse models, nanomedicines efficiently silenced the target genes and decreased the expression of abnormal Aβ and hyperphosphorylated Tau, respectively. Moreover, the co-delivered Rutin inhibited the Aβ aggregation and normalized the functions of microglia and astrocytes to reduce neuroinflammation, synergistically recovering the memory and cognitive deficits of AD mice, comparable to that of wide type mice. The successful AD treatment using the dual-targeted LDH nanomedicines provides a paradigm for the development of multi-targeted nanomedicines and warrants further study to combat AD with the complex pathogenic mechanisms. Graphical Abstract: Layered double hydroxide-based nanomedicines that are loaded with the BACE1/GSK3β siRNA and the natural compound Rutin and surface-modified with Ang2 and RVG29 efficiently penetrate the blood-brain barrier and target neurons. The dual-targeting nanomedicines simultaneously reduce the abnormal Aβ/Tau burden and neuroinflammation, successfully rescuing the memory and cognition deficient in Alzheimer's disease mice. ga1 Highlights: Nanomedicines co-deliver with siRNA and natural compound Rutin for synergistic treatment AD. These nanomedicines successfully reduce Aβ/Tau burden and neuroinflammation in AD mice. The memory and cognitive repairment in both APP/PS1 and Tau.P301S AD mice are significantly improved. Our study provides a paradigm for the design of multi-targeted nanomedicines to combat neurodegenerative diseases.